Improving Learning Outcomes through the TARL Approach in Teaching the Application of Pancasila Values in Daily Life: A Case Study of Grade V Students - Arisman Sabir; Larisman; Yanti Murni; Aldino; Septian Raibowo; Desi Fitria (Jurnal Ilmiah Sekolah Dasar, 2025)
Low achievement in understanding and applying Pancasila values indicates insufficiently contextual and adaptive instruction, limiting students’ critical thinking development.This study aims to analyze and examine the effectiveness of the Teaching at the Right Level (TaRL) approach in improving students’ learning outcomes and critical thinking skills in Pancasila Education. This research employed Classroom Action Research (CAR) involving 28 fifth-grade students as research subjects. The TaRL approach was implemented by adjusting learning strategies and activities based on students’ actual levels of understanding and ability. Data were collected through classroom observations, learning outcome tests, and interviews with teachers and students, using observation sheets, test instruments, and interview guidelines. The data were analyzed using descriptive quantitative and qualitative methods. The results showed a significant improvement in students’ learning outcomes, as indicated by an increase in learning mastery from 25% in the pre-cycle to 64% in Cycle I and reaching 86% in Cycle II. These findings confirm that the TaRL approach is effective in improving learning outcomes in Pancasila Education. Implicatively, the TaRL approach has the potential to serve as an adaptive and inclusive instructional strategy to support equitable competency achievement and strengthen character education at the elementary school level.